Association Between Nurses' Comfort and Confidence in Pain Management and Compassion Satisfaction and Fatigue...2024 American Society for Pain Management Nursing (ASPMN) Annual Conference, October 16-19, 2024, San Antonio, TX. - Schuller, Kristin A.; Burke, Ebru Cayir (Pain Management Nursing, 2025)
A current challenge that may exacerbate symptoms of compassion fatigue and compromise the ability to experience compassion satisfaction among nurses is pain management. This study examined the associations between nurses' comfort with administering pain management, confidence in providers' prescribing patterns and reported compassion satisfaction and compassion fatigue (measured as burnout and secondary traumatic stress). This exploratory study used a survey design to gather primary data from nurses via a convenience sampling method. A survey was created and disseminated electronically to registered nurses from September to November 2019. The survey asked about nurses' comfort administering pain medications, confidence in providers' prescribing patterns, and the Professional Quality of Life Scale (ProQOL). While nurses reported comfort treating patients with pain and managing pain, they were less confident that providers opioid prescribing patterns. Confidence in provider prescribing was positively correlated with compassion satisfaction and negatively correlated with burnout. Organizations should focus on continuing education of pain management, creating a culture of evidence-based pain management, and promoting effective communication.